Barriers to comprehensive nutrition care for cancer patients: a review - K. P., Bavika; B. S., Anantha Krishna; M., Mithesh; K. S., Praveen (International Journal Of Community Medicine And Public Health, 2024)
This comprehensive review studies the multifaceted barriers that delay cancer patients from accessing adequate nutrition throughout their cancer journey. Addressing these barriers is paramount, considering their profound implications on treatment efficacy, patient well-being, and overall outcomes. The analysis encompasses a range of obstacles comprises physiological, psychological, economic, social, and healthcare system factors, highlighting their intricate impact on nutritional intake and patient care. The exploration of nutritional barriers reveals a landscape encompassing challenges such as malnutrition, treatment-related side effects, psychological distress, physical limitations, lack of knowledge, cultural influences, financial constraints, and limited access to specialised nutritional support. These hurdles, if left unaddressed, can lead to adverse consequences including malnutrition, weakened immunity, impaired treatment response, decreased quality of life, and ultimately, poorer prognosis. The intricate interplay between inadequate nutrition and cancer outcomes is underscored, emphasising the pivotal role of proper nutrition in boosting the immune system, supporting treatment effectiveness, and hastening recovery. Strategies to overcome these barriers emerge through multidisciplinary approaches integrating medical and nutritional needs, personalised dietary plans, psychosocial support, and the integration of yoga and wellness practices to foster mindful eating and holistic well-being. This review provides valuable insights into the complexities of nutritional barriers in cancer care and emphasizes the critical need for comprehensive strategies to ensure cancer patients receive the vital nutritional support necessary for optimizing their journey through treatment and recovery.